2016
DOI: 10.1103/physrevb.94.180105
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure, stability, and optoelectronic properties of the organic-inorganic wide-band-gap perovskite CH3NH3BaI3 : Candidate for transparent conductor applications

Abstract: Structural stability, electronic structure and optical properties of CH3NH3BaI3 hybrid perovskite is examined from theory as well as experiment. Solution-processed thin films of CH3NH3BaI3 exhibited a high transparency in the wavelength range of 400 nm to 825 nm (1.5 eV to 3.1 eV for which the photon current density is highest in the solar spectrum) which essentially justifies a high bandgap of 4 eV obtained by theoretical estimation. Also, the XRD patterns of the thin films match well with the {00l } peaks of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 41 publications
(52 reference statements)
0
33
0
Order By: Relevance
“…Ap lane-wave energy cut-off of 500 eV was used for all the calculations. [15] Although the study of MA + cation is out of the scope of the present study,o ur past studies [16] have revealed that in the tetragonal phase, the most stable structure is when the adjacent MA + cation are perpendicular to each other.T om ake the present study accurate, we have used the most symmetric MA + alignment (along the 100d irection) in the cubic phase and most stable perpendicular alignment of neighbouring CÀNdipoles in the tetragonal phase. The Brillouin zone sampling was done by using an automated G (gamma)-centred K-point mesh.…”
Section: Synthesis Of Mapbx 3 Nanoparticlesmentioning
confidence: 88%
“…Ap lane-wave energy cut-off of 500 eV was used for all the calculations. [15] Although the study of MA + cation is out of the scope of the present study,o ur past studies [16] have revealed that in the tetragonal phase, the most stable structure is when the adjacent MA + cation are perpendicular to each other.T om ake the present study accurate, we have used the most symmetric MA + alignment (along the 100d irection) in the cubic phase and most stable perpendicular alignment of neighbouring CÀNdipoles in the tetragonal phase. The Brillouin zone sampling was done by using an automated G (gamma)-centred K-point mesh.…”
Section: Synthesis Of Mapbx 3 Nanoparticlesmentioning
confidence: 88%
“…shorter wavelength light, with increasing mixing content. There exist other first-principles calculations of optical properties for CsSnI 3 [131], CsPbX 3 [132], MASnX 3 [133] and MABaI 3 [134].…”
Section: Dielectric Constant and Photoabsorption Coefficientmentioning
confidence: 99%
“…[48][49][50][51][52] Alternatively, one can consider to transmute two divalent Pb 2+ ions into one monovalent ion M + and one trivalent ion M 3+ , i.e., 2Pb 2+ → M + + M 3+ , by keeping the total number of valance electrons unchanged at M IV sites. Known as atomic transmutation, this design strategy has led to great success in finding new materials with improved functionalities such as solar absorbers.…”
Section: Introductionmentioning
confidence: 99%